Do institutional or subject referencing style choices create barriers for students with specific learning disability? - Watkins, Fiona (Journal of learning development in higher education, 2023)
Models of information literacy (Coonan et al., 2018; SCONUL, 2011) are explicit: critical thinking and ethical information use are essential skills within higher education (HE). Referencing is key to this, demonstrating how students select and apply information to create knowledge (Buckley, 2015; Angelil-Carter, 1995). Within HE there has been an increased focus on inclusivity and accessibility (Equality Act, 2010; United Nations, 2015; Department for Education and Department for Health, 2015). Growing numbers of students are declaring a disability (Advance HE, 2019) and reports suggest they are increasingly dissatisfied with their courses (Office for Students, 2020). Proportionally, students with disabilities achieve lower grades than students without (Advance HE, 2019), suggesting needs and expectations of students with a disability are not being met within HE provisions. The presentation discussed an ethically approved small-scale mixed-methods study carried out as part of a MA in Special Educational Needs and Inclusion. The research investigated student perceptions of referencing, whether adherence to specific referencing styles is a barrier for students with dyslexia and began investigating the impact of referencing styles on reading comprehension. The largest disability declared within HE is Specific Learning Disability (SpLD) (Advance HE, 2019), which includes dyslexia (American Psychological Association, 2013). Students with SpLD report lower confidence with academic writing than non-SpLD students (Kinder and Elander, 2012). Academic literacy skills are arguably intertwined with a sense of legitimacy and belonging (Gourlay, 2009): it is therefore vital to consider ways of improving inclusion for all students (Office for Students, 2020). The presenter observed that students with SpLD spent more time and energy on referencing than their non-disabled peers. This perception is corroborated by others (Sanders, 2010) and when combined with slower reading speeds (Hendricks and Quinn, 2000; Sanders, 2010; Serry et al., 2018) reduces time students have for critical subject engagement (Wengelin, 2007). Attendees gained an understanding of how students view referencing and whether the choice of referencing system disadvantages students with dyslexia. Attendees also took part in a reading comprehension test giving a taster of the next steps for research which requires collaborative partners.